2011
DOI: 10.1111/j.1745-9125.2011.00244.x
|View full text |Cite
|
Sign up to set email alerts
|

Decomposing the Peer Effect on Adolescent Substance Use: Mediation, Nonlinearity, and Differential Nonlinearity*

Abstract: Although the correlation between peer delinquency and delinquency is one of the most consistently demonstrated findings in delinquency research, researchers have focused primarily on the direct, linear, and additive effects of peers in statistical models, rather than on empirically modeling mediating, nonlinear, and moderating processes that are specified by theory. To address these issues, we measure respondent delinquency and peer delinquency with illegal substance use and then decompose the effect of peer s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 100 publications
(113 reference statements)
4
26
0
1
Order By: Relevance
“…Once this threshold is met, an increase of half a standard deviation is associated with a 5.12% decrease in personal offending, followed by a decrease of 14.15%. This finding comports with previous research based on traditional peer groups and illustrates the functional form of peer exposure is indeed nonlinear (Zimmerman & Messner, 2011;Zimmerman & Vásquez, 2011).…”
Section: Analytic Strategysupporting
confidence: 90%
See 4 more Smart Citations
“…Once this threshold is met, an increase of half a standard deviation is associated with a 5.12% decrease in personal offending, followed by a decrease of 14.15%. This finding comports with previous research based on traditional peer groups and illustrates the functional form of peer exposure is indeed nonlinear (Zimmerman & Messner, 2011;Zimmerman & Vásquez, 2011).…”
Section: Analytic Strategysupporting
confidence: 90%
“…Using data from the Project on Human Development in Chicago Neighborhoods (PHDCN), their findings support this claim, indicating the effect of exposure to peer violence on selfreported violence becomes weaker at very high levels of exposure to peer delinquency. In a subsequent study using the same data, Zimmerman and Vásquez (2011) reported a similar nonlinear relationship between substance using peers and individual substance use. Research by Burt and Rees (2014) comports with these findings, suggesting the association between individual substance use and exposure to peer substance use was nonlinear.…”
Section: Nonlinearity In Traditional Networkmentioning
confidence: 51%
See 3 more Smart Citations